The faces of terrorism : social and psychological dimensions - Smelser, Neil J. (Science essentials (National Academy of Sciences (U.S.)), 2007)
Terrorism is the most clear and present danger we confront today, yet no phenomenon is more poorly understood by policymakers, the media, and the general public. The Faces of Terrorism is the first serious interdisciplinary examination of terrorism in all its facets. What gives rise to it, who are its proponents and how do they think, and how--and why--does it work? Neil Smelser begins by tackling the fundamental problem of defining what exactly terrorism is. He shows why a precise definition has eluded us until now, and he proposes one that takes into account the full complexities of this unc.